Changes in pathology test ordering by early career general practitioners: a longitudinal study. Issue 2 (17th July 2017) - Magin, Parker J; Tapley, Amanda; Morgan, Simon; Henderson, Kim; Holliday, Elizabeth G; Davey, Andrew R; Ball, Jean; Catzikiris, Nigel F; Mulquiney, Katie J; van Driel, Mieke L
Abstract: Objective: To assess the number of pathology tests ordered by general practice registrars during their first 18–24 months of clinical general practice. Design: Longitudinal analysis of ten rounds of data collection (2010–2014) for the Registrar Clinical Encounters in Training (ReCEnT) study, an ongoing, multicentre, cohort study of general practice registrars in Australia. The principal analysis employed negative binomial regression in a generalised estimating equations framework (to account for repeated measures on registrars). Setting, participants: General practice registrars in training posts with five of 17 general practice regional training providers in five Australian states. The registrar participation rate was 96.4%. Main outcome measure: Number of pathology tests requested per consultation. The time unit for analysis was the registrar training term (the 6‐month full‐time equivalent component of clinical training); registrars contributed data for up to four training terms. Results: 876 registrars contributed data for 114 584 consultations. The number of pathology tests requested increased by 11% (95% CI, 8–15%; P < 0.001) per training term. Conclusions: Contrary to expectations, pathology test ordering by general practice registrars increased significantly during their first 2 years of clinical practice. This causes concerns about overtesting. As established general practitioners order fewer tests than registrars, test ordering may peak during late vocational training and early career practice. Registrars need support during this difficult period in the development of their clinical practice patterns.